The Process of Making an Item of Palace Furniture in the 1830-1850s According to Russian State Historical Archives Data - Torbik, Vladimir S. (Actual Problems of Theory and History of Art, 2018)
Based on the analysis of archive documents, the article examines factors of influence on creation of a subject of applied art, i.e. a piece of furniture. It explores documents shedding light on the role and influence of a customer on nature of a future work of art. They reveal hard work at every stage and difficulties in relations of an architect and contractors of projects. Short deadlines required attraction of a large number of contractors, and naturally not all of them met high demands of an architect. The documents evince how difficult it was for an architect to achieve the desirable result. Alongside with this, the article discloses such a stage of creation of a subject of art as acceptance of its model. Unlike in case with architectural models, in case with furniture it was one subject from a batch which served as a model — a sample, after adjustment or acceptance of which the project was finally affirmed.
Keywords: project; interior; furniture; A. de Montferrand; A. Stakenschneider